2019
DOI: 10.21608/ejabf.2019.47385
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Molecular Identification of Genus Dicentrarchus Using Mitochondrial Genes and Internal Transcribed Spacer Region

Abstract: DNA barcoding is one of the powerful DNA-based identification tools that are used for accurate identification of a species. Despite several DNA barcodes were used, the accuracy and suitability of these barcodes depend on speciesspecific variations.The current study was conducted to compare the efficiency of two mitochondrial genes to the nuclear Internal Transcribed Spacer (ITS) region in the molecular identification of genus Dicentrarchus. A total of 80 fish samples for Dicentrarchus labrax and Dicentrarchus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…DNA barcoding has been widely used for delineating species boundaries, discriminating closely related species of fish (Hajibabaei et al 2007a). Similarity or percentage identity ranged from 99-100% with the identified species in the GenBank databases that was commonly recorded among the fish species and demonstrated the potency of such genomic technique in confirming individual fish similarity (Debenedetti et al 2014;Bellagamba et al 2015;Abbas et al 2017;Ali et al 2019a;Ali et al 2020;Ibrahim et al 2020). On the nucleotide level, the sequence alignment detected considerable polymorphism at different consensus positions in 28 fish species, the differences had been widely verified (Persis et al 2009).…”
Section: Discussionmentioning
confidence: 88%
“…DNA barcoding has been widely used for delineating species boundaries, discriminating closely related species of fish (Hajibabaei et al 2007a). Similarity or percentage identity ranged from 99-100% with the identified species in the GenBank databases that was commonly recorded among the fish species and demonstrated the potency of such genomic technique in confirming individual fish similarity (Debenedetti et al 2014;Bellagamba et al 2015;Abbas et al 2017;Ali et al 2019a;Ali et al 2020;Ibrahim et al 2020). On the nucleotide level, the sequence alignment detected considerable polymorphism at different consensus positions in 28 fish species, the differences had been widely verified (Persis et al 2009).…”
Section: Discussionmentioning
confidence: 88%
“…Many studies have reported that a lack of database species (DNA barcodes) can influence the accuracy of species identification (Deichmann et al 2017). DNA barcoding has effectively differentiated organisms up to the species level (Lakra et al 2016;van der Walt et al 2017;Bingpeng et al 2018;Ali et al 2019).…”
Section: Molecular Analysismentioning
confidence: 99%
“…DNA barcoding applies universal primers to amplify a targeted genomic region. The efficiency of this method depends on the diverse nature of the targeted region among species [22,23]. In crustaceans, targeting the region of the cytochrome oxidase subunit I (COI) mitochondrial gene using the primer pairs described by Folmer et al [24] was the most efficient.…”
Section: Introductionmentioning
confidence: 99%